THE RELATIONSHIP BETWEEN SELF-CONFIDENCE ANDSPEAKING PERFORMA NCE OF SECOND SEMESTER STUDENTS OF ENGLISH DEPARTMENT AT UNISMA - Fatma Asyura (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT: This thesis is discussing about the relationship between self confidence and students’ speaking performance, whether there is correlation between students’ self confidence and their speaking performance or not. The objective of this study is to know the relationship between students’ self confidence and their speaking performance. Quantitative research approach was used in this research by using correlation research. The population is all the second semester students of English Department in University of Islam Malang. All the students of second semester have an equal opportunity.Clustered random sampling was used in this research to take the sample based on lottery. The instrument of this research is questionnaire which was adopted from Griffee (1997). The obtained data was analyzed by using SPSS (Statistical Package for Social Science) 20.0. To reach the objective of the present study, the researcher formulates the research problem as “is there any correlation between self-confidence and speaking performance of the second semester students of English Department at University of Islam Malang?”.The table of correlation reported that Pearson Correlation (r) which represents the correlation between self-confidence and speaking performance is .076. Afterward, the level of significance is at .591 which means P-value is higher than .05. It means that the null hypothesis was accepted and the alternative hypothesis was rejected. In other words, there was no significant correlation between students’ self-confidence and their speaking achievement of the second semester students of English Department at UNISMA. It can be interpreted that the students’ self confidence can not predict their speaking performance. Keywords: self confidence, speaking performance, speaking, correlation